Short-term effects of cover crops on soil properties and macrofauna - Scaglione, Josefina; Montico, Sergio; Montero, Guillermo (Ecosistemas y Recursos Agropecuarios, 2023)
The assessment of edaphic changes due to the adoption of different management practices requires the analysis of different types of variables. The aim of this study was to determine annual variations on soil properties and macrofauna, and the interactions between them, in cropping sequences with and without cover crops (CC). The work was carried out on an experiment installed in Zavalla (Santa Fe, Argentina) and the treatments included CC (vetch and triticale) and fallow before corn and soybean, respectively. We determined soil organic carbon (SOC) and particulate organic carbon (POC), percentage of water stable aggregates (WSA), pH and macrofauna communities’ parameters and trophic groups abundance. Treatments which included CC showed higher values of POC and WSA as compared to fallow ones, while SOC presented an annual increment in all treatments. As regard to macrofauna communities’ parameters, CC of vetch made favorable changes in abundance, richness and diversity after its cycle, while CC of triticale showed a similar response to fallow and values were lower than vetch ones. Trophic groups abundance showed seasonal variations and changes associated with crop sequences characteristics. CC caused short-term changes on soil properties and macrofauna due to the coverage and the contribution of organic materials.